2015
DOI: 10.1108/oclc-02-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Making journals accessible front & back: examining open journal systems at CSU Northridge

Abstract: Purpose – This study aims to examine Public Knowledge Project (PKP) Open Journal Systems (OJS) for its overall web accessibility and compliance with the Federal Electronic and Information Technology Accessibility and Compliance Act, also known as Section 508. Design/methodology/approach – Twenty-one individual web pages in the CSUN test instance of PKP’s OJS version 2.4.0 used in three back-end journal development user roles were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…There are tools for testing web accessibility that a journal team can utilize in evaluating hosting platforms. Borchard et al (2015) have reported using WAVE, Fangs and Functional Accessibility Evaluator tools to test web‐accessibility tools of OJS. Clarivate also stipulates that the information architecture of a journal's website must facilitate easy navigation across all the journal's content (Clarivate, 2019).…”
Section: Technical Decisions and Logistical Considerationsmentioning
confidence: 99%
“…There are tools for testing web accessibility that a journal team can utilize in evaluating hosting platforms. Borchard et al (2015) have reported using WAVE, Fangs and Functional Accessibility Evaluator tools to test web‐accessibility tools of OJS. Clarivate also stipulates that the information architecture of a journal's website must facilitate easy navigation across all the journal's content (Clarivate, 2019).…”
Section: Technical Decisions and Logistical Considerationsmentioning
confidence: 99%
“…While very few identified lack of expertise as their primary challenge, 60.9 percent said a lack of expertise about readers acted as a barrier to improving design "Sometimes" or "Always." Although most respondents identified multiple sources of expertise, further analysis shows that 28 services (43.8%) did not have any expertise for understanding readers in the library (inside or outside a publishing unit), and nearly all of those (26,40.6% of respondents) lack that expertise even when looking to the university as a whole. In other words, most expertise is external-from vendors, colleagues at other institutions, or previous studies-and these library publishing services have little capacity to assess reader needs directly.…”
Section: Variety Of Activitiesmentioning
confidence: 99%
“…They found the front end to meet basic accessibility needs for readers. 26 Beyond issues for those with disabilities, interface design and related reading issues, which were not particularly prominent at the first Library Publishing Forum, did get scattered mention at the second.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customizable, fleksibel, dapat diperluas secara umum dan banyak alasan untuk menggunakan Drupal sebagai mesin untuk membangun sebuah website, Mengembangkan journal directory dan isi artikelnya menggunakan website Drupal bisa dilakukan dengan mudah. Namun, karena journal directory yang dibangun dengan CMF Drupal, maka manajemen penerbitan secara elektronik tidak dimiliki dan hanya menfokuskan pada journal directory.Selain itu, penelitian juga dilakukan olehBorchard, et al (2015). Penelitian ini bertujuan untuk menguji sistem informasi Public Knowledge Project (PKP) Open Journal Systems (OJS) untuk aksesibilitas keseluruhan web dengan hukum Federal Electronic and Information Technology Accessibility and Compliance pada CSU Northridge.…”
unclassified